REVIEW: POLYCYCLIC AROMATIC HYDROCARBON CONTAMINATION IN MARINE LIFE AND ITS IMPLICATIONS FOR FOOD SAFETY AND PUBLIC HEALTH: REVIEW : KONTAMINASI POLIKLIK HIDROKARBON AROMATIK PADA BIOTA LAUT DAN IMPLIKASINYA TERHADAP KEAMANAN PANGAN SERTA KESEHATAN MASYARAKAT - Fauziah Hasdin; Wahyuni Agus (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Polycyclic Aromatic Hydrocarbons (PAHs) are persistent organic compounds that extensively contaminate marine environments as a result of anthropogenic activities such as industrial processes, transportation, fossil fuel combustion, and petroleum exploration. The hydrophobic and lipophilic properties of PAHs enable these compounds to accumulate easily in sediments and marine biota tissues, thereby increasing their potential to enter the human food chain. This article aims to examine PAH contamination in marine biota and its impacts on food safety and public health. The study employed a narrative review approach by analyzing scientific publications published between 2015 and 2025 obtained from PubMed, ScienceDirect, and Google Scholar databases. The review findings indicate that PAHs in marine environments originate from both petrogenic and pyrogenic sources and subsequently accumulate in aquatic organisms through bioaccumulation and biomagnification processes. Exposure to PAHs in marine biota causes oxidative stress, reproductive disorders, tissue damage, and deterioration of aquatic ecosystem quality. Furthermore, the consumption of seafood contaminated with PAHs may increase the risk of cancer, immune system disorders, and other health problems in humans. Therefore, PAH contamination in marine environments represents a serious threat to food safety and public health. Environmental monitoring, pollution source control, and the implementation of stricter food safety regulations are essential to minimize the adverse impacts of PAHs on ecosystems and human health.